2016
DOI: 10.1245/s10434-015-5079-x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of a New Nonradioactive Surgical Guidance Technology for Locating Nonpalpable Breast Lesions

Abstract: These data suggest that the SCOUT system is safe and effective for guiding the excision of nonpalpable breast lesions and a viable alternative to standard localization options. A larger prospective, multi-institution trial of SCOUT currently is underway to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 24 publications
5
61
1
Order By: Relevance
“…The Savi Scout surgical guidance system (Cianna Medical, Aliso Viejo, Calif) is an alternative method to localize and excise nonpalpable breast lesions (15,16). Savi Scout helps the radiologist to implant an infrared-activated, electromagnetic wave reflector device (referred to as a reflector) into the breast with image guidance, which can then be percutaneously detected by using a handpiece-and-console system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Savi Scout surgical guidance system (Cianna Medical, Aliso Viejo, Calif) is an alternative method to localize and excise nonpalpable breast lesions (15,16). Savi Scout helps the radiologist to implant an infrared-activated, electromagnetic wave reflector device (referred to as a reflector) into the breast with image guidance, which can then be percutaneously detected by using a handpiece-and-console system.…”
Section: Methodsmentioning
confidence: 99%
“…Placement of the Savi Scout reflector deeper than 4.5 cm may interfere with detection according to the manufacturer; the initial pilot study reported difficulty with detection of two reflectors at 4.5-and 6-cm deep (16). This is a potential limitation of the system.…”
Section: Breast Imaging: Reflector-guided Breast Lesion Localization mentioning
confidence: 99%
See 1 more Smart Citation
“…The audible and numerical signals change with increasing proximity to the lesion, directing precise localization. 10 A pilot study by Cox et al 11 in June 2016 reported the use of the SAVI SCOUT system for preoperative breast localization in 50 patients. This showed that the system was safe and effective, with all of the lesions and reflectors successfully removed and no adverse outcomes.…”
Section: Savi Scoutmentioning
confidence: 99%
“…1 The technique uses a small implantable device placed through a needle via ultrasound or stereotactic guidance, similar to current radiologic localization techniques. Once implanted, the device is activated by infrared light from the handpiece, and an electromagnetic wave is reflected back to the console.…”
mentioning
confidence: 99%